HUBUNGAN SHIFT KERJA DENGAN STRES KERJA PADA KARYAWAN BAGIAN OPERATION PT. NEWMONT NUSA TENGGARA DI KABUPATEN SUMBAWA BARAT - Firmana, Andri Andri Satriadi Firmana, Widodo Hariyono; Hariyono, Widodo (Universitas Ahmad Dahlan, 2011)
Background: Work shift is one of major source of job stress for workers that affect the biological, psychological and social life. Stress can happen in a short notice, but also can happen in a long moment. The excessive stress to threaten a persons ability to cope with the environment. The objective of this study is to determine the relationship shifts with work stress on the operation of PT. Newmont Nusa Tenggara in West Sumbawa regency. Method: This was an observational research with cross sectional design. The population of this study consists of 250 employees of the operation crew A of PT. Newmont Nusa Tenggara. The research sample is some staff the operation crew of A PT. Newmont Nusa Tenggara. The sampling used is proportionate with stratified random sampling technique. The sample takes 71 people. Analysis of descriptive data using frequency distribution tables and analytically to determine the relationship between two variables with bivariate data analysis, chi-square test. Result: The results showed a significant relationship between work shift and work stress with chi square value of 5.329 compared with T-score tables 3, 841 on df = 1 at ? = 5 percent (0.05) and prevalence ratio (RP) = 2065 (95% CI = 1.093-3.89), so that Ho refused and Ha accepted. Conclusion: : Independent variables studied (work shift) has a significant relationship to job stress. Keywords: Work shift, Work stress